Pancreatic endometriosis a rare entity in surgery: a case report - Gutiérrez, Carlos Durán; Rios Muñoz, Braulio (International Surgery Journal, 2024)
Endometriosis is a rare entity that occurs in 2 to 10% of women of childbearing age. It may be rarer if it occurs in extrapelvic organs and extremely rarely in pancreatic tissue, and it may be confused with other causes of pancreatitis or pancreatic pathologies. In the following case we present a young woman of childbearing age who is admitted with abdominal pain. She mentions having recently had elevated pancreatic enzymes. At the time of evaluation within normal parameters, a pancreatic cyst is suspected, which is why it is She underwent surgical treatment, however, due to clinical signs, a cyst with the appearance of endometriosis was punctured, and the histopathological report confirmed pancreatic endometriosis, an entity little known in surgery, however, with a favorable outcome after surgical intervention.